Transcriptomic Analysis of the Association Between Diabetes Mellitus and Myocardial Infarction - Song, Lijuan; You, Wenjun; Wang, Peng; Li, Feng; Liu, Huakun (Experimental and Clinical Endocrinology & Diabetes, 2019)
Background Diabetes mellitus (DM) is a major risk factor for coronary artery disease (CAD), and the complications of CAD are the leading cause of deaths among people with DM. Herein, this study aims to identify the common genes and pathways between diabetes and myocardial infarction (MI) to provide more clues for the related mechanism studies.Methods Differentially expressed genes (DEGs) were identified using the cutoff (|log2(fold change)|>0.45 and P value<0.05) by the analysis of online datasets (GSE9006 and GSE48060) related to DM and MI respectively. Moreover, the overlapped DEGs between DM and MI were identified, followed by enriched Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis. And the independent patient RNA samples were collected for qRT-PCR validation of the mRNA expression of these overlapped genes.Results PI3, ACSL1, MMD and MMP were altered in both T1DM and MI, and they were highly related to “regulation of cellular protein metabolic process”. Meanwhile, six genes were identified in both T2DM and MI, which are ADM, NFIL3, PI3, SLPI, ACSL1 and MMP9 and significantly related to “negative regulation of endopeptidase activity”. And the expression of these genes were validated.Conclusions In summary, we identified the common DEGs and pathways between T1DM or T2DM and MI, and further validated the changes of those DEGs, providing some clues for mechanism study and potentially therapeutic targets.
Keywords: diabetes mellitus; myocardial infarction; gene signature; risk factor; peripheral blood